Batu City Tourist Village: the Effect of Destination Image on Tourist Satisfaction and Revisit Intention - Muhammad Syarif Hidayatullah Elmas; Widji Astuti; Mokhamad Natsir (Indonesian Journal of Business Analytics, 2024)
The research purpose is to analyzing the effect of destination image on tourist satisfaction, analyzing the effect of destination image on revisit intention, analyzing the effect of tourist satisfaction on revisit intention, and analyzing tourist satisfaction mediates the effect of destination image on revisit intention in the tourist village of Batu City. This study uses a quantitative explanatory research approach with the sample of this research is Indonesians who when the research was conducted finished traveling in the tourist village of Batu City and were at least 17 years old, totaling 155 respondents and using Structural Equetion Modeling (SEM) which will be processed using the AMOS (Analysis of moment structure) program. The results showed that destination image has a significant impact on tourist satisfaction and revisit intentions, tourist satisfaction has a significant impact on revisit intentions, and tourist satisfaction does not have a role as a mediator that forms the relationship between destination image and revisit intentions in the Batu City tourist village.